ChemInform Abstract: Characterization of Ax[W6I14] as Key Compounds for Ligand‐Substituted A2[W6I8L6] Clusters. Issue 52 (6th December 2016) - Hummel, Thorsten; Stroebele, Markus; Schmid, Dominic; Enseling, David; Juestel, Thomas; Meyer, H.‐Juergen
Abstract: Polycrystalline Mx [W6 I14 ] (M: Na, K, Rb, Cs) is prepared by solid state reaction of stoichiometric amounts of MI and W3 I12 (<95% yield).